Subcutaneous mastectomy with nipple-areolar preservation: new feasibilities of surgical treatment in patients with breast cancer - A. A. Volchenko (Опухоли женской репродуктивной системы, 2014)
The current surgical treatment strategy for breast cancer is to fulfill two tasks: a reliable cure for cancer and solution of esthetic problems. The former task is successfully solved by radical mastectomy whereas it is rather difficult to restore the breast because a specialist has to compensate for the whole volume of its tissue and to form a nipple-areolar complex (NAC) and a submammary fold. Subcutaneous mastectomy with and without NAC preservation optimally solves both tasks: its performance, by simultaneously maintaining the high level of radicalism, substantially makes primary breast repair easier and yields a better esthetic result.